2018
DOI: 10.1007/s13346-018-0486-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: pH-responsive CAP-co-poly(methacrylic acid)-based hydrogel as an efficient platform for controlled gastrointestinal delivery: fabrication, characterization, in vitro and in vivo toxicity evaluation

Abstract: Cellulose acetate phthalate-based pH-responsive hydrogel was synthesized for fabrication of polymeric matrix tablets for gastro-protective delivery of loxoprofen sodium. Cellulose acetate phthalate (CAP) was cross-linked with methacrylic acid (MAA) using free radical polymerization technique. Fourier transform infrared (FTIR) spectra confirmed the formation of cross-linked structure of CAP-co-poly(methacrylic acid). Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) confirmed the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…46 Due to the presence of chemical or physical cross-links, they are able to swell and retain large amounts of water, and preserving their structural and dimensional constrained integrity. 47 Hydrogels are biocompatible and biodegradable materials and have been used in cell therapy, drug delivery, biosensing, tissue engineering and wound healing [226][227][228][229] (Table 8).…”
Section: Smart Hydrogelsmentioning
confidence: 99%
“…46 Due to the presence of chemical or physical cross-links, they are able to swell and retain large amounts of water, and preserving their structural and dimensional constrained integrity. 47 Hydrogels are biocompatible and biodegradable materials and have been used in cell therapy, drug delivery, biosensing, tissue engineering and wound healing [226][227][228][229] (Table 8).…”
Section: Smart Hydrogelsmentioning
confidence: 99%
“…Biopolymers based hydrogels are biodegradable and biocompatible materials having potential in drug delivery applications and already reported in tissue engineering, ophthalmic, cell encapsulation, and wound healing [1] . The structural morphology demonstrate that macromolecular polymer gels formulated of cross‐linked polymer networks exhibit effectiveness towards various requisitions [212–215] . Pietramaggiori et al fabricated a matrix system through Poly‐N‐acetyl glucosamine hydrogel obtained from microalgae [216] .…”
Section: Biopolymer Centered Materials For Different Biomedical Applimentioning
confidence: 99%
“…Pietramaggiori et al fabricated a matrix system through Poly‐N‐acetyl glucosamine hydrogel obtained from microalgae [216] . The developed hydrogel matrix is approved by Food and Drug Administration for treating the patients suffering from diabetic foot ulcers [215–217] . It has been reported that hydrogels is found proficient towards the healing capability of wounds with lowest exudates.…”
Section: Biopolymer Centered Materials For Different Biomedical Applimentioning
confidence: 99%
See 2 more Smart Citations